Expensive words, cheap images: 'Scripting' the adapted screenplay. (29th August 2012) - Munt, Alex
This article explores 'scripting' the adapted screenplay for budget film models, including microbudget features, DIY film-making and creative practice-led research. It highlights the lack of attention given to the adapted screenplay in the field of adaptation studies, and works with notions of intermediality, and transmediality, to privilege the screenplay as the primary site for creative interaction in the adaptation process. In the context of small-scale, budget film-making practices the focus is towards modes of scripting that rely on working with images, both as part of the screenplay form/format and more directly, in 'writing' with moving images, with the screenplay situated within production. This article argues that in consideration of the adapted screenplay, for budget film-making, the relationship between words and images is realigned. The impact of digital media culture together with the advance of digital film-making will accelerate this. Two case studies are presented. The first is Mala No he (1985), the debut feature film of Gus Van Sant, based on the novella by Walt Curtis. The second is LBF (2011), the author's own debut feature film, based on the novel Living Between Fucks (2006) by Cry Bloxsome. This article aims to engage screenwriting researchers, independent/budget film-makers and creative arts practitioners.